A Parallel Computational Model for Three-Dimensional, Thermo-Mechanical Stokes Flow Simulations of Glaciers and Ice Sheets (Communications in Computational Physics, 2014)
This paper focuses on the development of an efficient, three-dimensional,thermo-mechanical, nonlinear-Stokes flow computational model for ice sheet simulation. The model is based on the parallel finite element model developed in [14] whichfeatures high-order accurate finite element discretizations on variable resolution grids.Here, we add an improved iterative solution method for treating the nonlinearity of theStokes problem, a new high-order accurate finite element solver for the temperatureequation, and a new conservative finite volume solver for handling mass conservation.The result is an accurate and efficient numerical model for thermo-mechanical glacierand ice-sheet simulations. We demonstrate the improved efficiency of the Stokes solverusing the ISMIP-HOM Benchmark experiments and a realistic test case for the Greenland ice-sheet. We also apply our model to the EISMINT-II benchmark experimentsand demonstrate stable thermo-mechanical ice sheet evolution on both structured andunstructured meshes. Notably, we find no evidence for the "cold spoke" instabilitiesobserved for these same experiments when using finite difference, shallow-ice approximation models on structured grids.